A saturated treatment model for the transmission dynamics of rabies / Ayoade Abayomi Ayotunde … [et al.] - Ayoade, Abayomi Ayotunde; Peter, Olumuyiwa James; Ayoola, Tokunbo Aderemi; Victor, A. A. (Penerbit UiTM, 2019)
Rabies is a viral disease that claims about 59 000 lives globally every year. The ignorance of the fact that man can be a carrier of the disease makes every practical and theoretical approach towards the study of the disease a good development. In this work, a mathematical model is designed to incorporate a saturated incidence rate such that the incidence rate is saturated around the infectious agents. The model is studied qualitatively via stability theory of nonlinear differential equations to assess the effects of general awareness, constant vaccination and the saturated treatment on the transmission dynamics of rabies disease. The effective reproduction number is derived and the numerical simulation is carried out to verify the analytical results. It is discovered that while general awareness plays pivotal roles in averting rabies death, multiple control measures have the tendency of driving rabies to extinction.